ИСТОРИЯ И МЕСТО ПЕСОЧНОЙ ТЕРАПИИ В СИСТЕМЕ ПСИХОТЕРАПЕВТИЧЕСКИХ МЕТОДОВ - Khachibabyan , S. S. (Modern Psychology, 2018)
This article is devoted to the history of origins and development of sand therapy, as well as its role in the modern psychotherapy. In the context of brief historical outline the main characteristics of approaches of the founders of sand therapy such as C. Jung, M. Lowenfeld, D. Kalff have been covered. Within the scope of the article we also tried to briefly describe the methods of sand painting and sand animation as a developing technique in psychotherapeutic work.
Keywords: art therapy; sand therapy; “sand world”; sand drawing